The Values of Local Wisdom in the Muang Jong (Salamat Laut) Tradition of the Sawang Tribe in Selinsing Village, Belitung Timur Regency - Dandy Rinaldo; Trisna Sukmayadi (Jurnal Civicus, 2022)
As the era of globalization goes on in the entire order of the nation's life, it requires the Indonesian state to be aware of things that have a negative impact, such as the impact of the development of anti-character values. The development and preservation of cultural values and local wisdom is very much needed. This study aims to describe the values of local wisdom in the Muang Jong (sea salvation) tradition of the Sawang tribe in Selinssing Village, East Belitung Regency. This study uses a qualitative approach with the type of descriptive research. Data collection techniques were carried out using interviews and observations. The data obtained in this study were analyzed through data reduction, data display, and drawing conclusions/verification. The results of this study show that 1) the background of the Muang Jong tradition is that it started when the Sawang people were in the ocean and they got a disaster where they were finally saved by the God of the Sea. After that incident, there was the Muang Jong tradition where this tradition is an expression of gratitude for the Sawang Tribe community to the God of the Ruler of the ocean. 2) The values of local wisdom contained in the Muang Jong tradition are spiritual values, religious values, mutual cooperation values, togetherness values, artistic values and historical values. 3) Efforts to preserve and introduce the values of local wisdom contained in the Muang Jong (sea safety) tradition of the Sawang Tribe is to collaborate with the local government to introduce the tradition through the tourism office and policies from the local government. In addition, to preserve the Muang Jong tradition for the youth of the Sawang Tribe is to directly involve the youth in a series of Muang Jong tradition activities.